Growth mindset and responses to acute stress - Fischer, Ethan; Fox, Cosette; Yoon, K. Lira (Taylor & Francis, 2023)
Individuals with high levels of growth mindsets believe that attributes are malleable. Although links between acute stress responses and growth mindsets of thought, emotion, and behaviour are central to the conceptualisation of psychological disorders and their treatment, such links have yet to be examined. Undergraduate participants (N = 135) completed a modified Trier Social Stress Test (TSST), and their salivary cortisol and anxiety were assessed throughout the session. Hierarchical linear models revealed that higher growth mindset of behaviour was associated with lower cortisol levels at 25-min after the TSST onset (i.e. peak cortisol stress reactivity) in men, but not in women. Considering one’s gender may be critical in understanding the relationship between growth mindset and stress responses.
Keywords: UMBC Affect, Cognition, & Emotional Disorders Lab (ACED Lab); acute stress anxiety cortisol Mindset Trier Social Stress Test